2017
DOI: 10.3390/nu9080914
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Therapy of Type 2 Diabetes—What Is the Potential of Daily Water Intake and Its Mineral Nutrients?

Abstract: We aim to present an overview of the possible influence of drinking water in general and mineral water in particular in improving glycemic parameters in persons with or without type 2 diabetes. We performed a literature search that produced 15 randomized controlled trials (RCTs) on this topic with mainly small sample sizes. We also discuss relevant observational and animal studies as well as the effects of important supplements in mineral water such as hydrogencarbonate and magnesium. There is low evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 67 publications
0
8
0
2
Order By: Relevance
“…The importance of healthy fluid intake in children for physical and mental performance and health and in the prevention of obesity has been discussed and practiced [1–4]. Ingredients contained in mineral water for consumption such as magnesium [5, 6], calcium [7], or both [8] and bicarbonate [9] have demonstrated their ameliorating effects on metabolic diseases or health promoting functions through cohort studies in multiple locations worldwide. On the other hand, minerals such as nickel have parallel effects on body fat accumulation [10].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of healthy fluid intake in children for physical and mental performance and health and in the prevention of obesity has been discussed and practiced [1–4]. Ingredients contained in mineral water for consumption such as magnesium [5, 6], calcium [7], or both [8] and bicarbonate [9] have demonstrated their ameliorating effects on metabolic diseases or health promoting functions through cohort studies in multiple locations worldwide. On the other hand, minerals such as nickel have parallel effects on body fat accumulation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that hydropinotherapy with sulphurous mineral water is effective to contrast metabolic disorders, especially T2D [ 19 , 42 ] and gastrointestinal diseases [ 20 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium is needed for β-cell function, is crucial for insulin signalling (is essential for the insulin-insulin receptor interaction, the affinity of the insulin receptor tyrosine kinase for ATP and the autophosphorylation of the β-subunits of the insulin receptor), has anti-inflammatory and anti-oxidant properties, plays a role in the regulation of glucocorticoid production and is a co-factor in intra- and extracellular lipid metabolism [9,28,91,99,159,160,161,162,163]. Bicarbonate, through correction of metabolic acidosis/counteraction of diet-induced acid load, improves insulin sensitivity and decreases glucocorticoid production [9,20,22,25,75,162]. Dietary calcium has been linked to anti-inflammatory and anti-oxidant properties, lipid metabolism towards its utilization, insulin sensitivity, increased thermogenesis, reduced glucocorticoid production and increased Sirt1 protein expression [9,164].…”
Section: Discussionmentioning
confidence: 99%